Norms for Eating Disorder Examination Questionnaire (EDE-Q) among Secondary School Students in Kuala Lumpur, Malaysia - Musa R; Bujang MA; Haniff J; Mohamad NA; Omar K; Radeef AS (International Islamic University Malaysia, 2024)
Non-Indexed Publication